Legal Education: Why Should a Lawyer Study Arts in a University? - Dunham, Allison (Victoria University of Wellington Law Review, 2019)
This article is a response to the report of the Committee of the Law Society recommending a reduction of the number of arts units from five to three. The author argues that the United States had increased arts education requirements for law students and New Zealand should follow suit. First, Dunham argues that an arts education provides professional pride as it allows for a broader scope of knowledge, understanding, and wise judgment. Secondly, he argues that an arts education safeguards the public by providing the lawyer with a broader understanding of human values and cultures which they should seek to obey. Finally, the author argues that an arts education is necessary for the competence of all lawyers by providing varied perspectives.